SCALING GLOBAL LOGISTICS OPERATIONS: THE POWER OF WEB PLATFORMS AND MICROSERVICES - Naveena Pathuri (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The development of supply chain activities calls for strong digital architectures supporting intricate worldwide logistics systems. This article investigates how contemporary web platforms and microservices architectures are changing established supply chain systems to allow unheard-of operational agility and scalability. Through a review of industry-leading implementations, especially with an eye toward Amazon's shift from monolithic systems and DHL's worldwide platform unification, the basic elements and strategic ideas to create strong logistics platforms. This article shows how modular service architecture and pipelines of constant integration and deployment help companies to change to meet market needs while preserving system dependability quickly. Leveraging industry knowledge and recorded case studies, this article offers a thorough architecture for creating microservices-based logistics systems, tackling important issues in service decommission data consistency and cross-border operations. While keeping the flexibility to incorporate new technologies, the results imply that companies using microservices architecture in their supply chain operations get notable increases in delivery efficiency, system scalability, and customer satisfaction. This article adds to the increasing corpus of information on contemporary supply chain architecture and advises companies considering comparable digital changes.